Blessings of Burntisland - Stanton, Jenny (Karnac Books, 2011)
Joe Fairlie is a treasure dowser. As the novel opens, he locates The Blessing of Burntisland, a seventeenth-century treasure barge sunk in the Firth of Forth off Scotland. The treasure of King Charles I has lain in the sea for decades; but so it seems have the spirits of two of the ship's survivors. At his moment of greatest triumph, Joe is assailed by the first of many waking dreams that plunge him into the life of one of the wreck's survivors, the court doctor, Thomas Newbolt, who is the antithesis of Joe. The other survivor is the magical boy, Robbie. In this picaresque novel of possession.